2013
DOI: 10.1016/j.ijid.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphisms in the CYP1A1, ACE, and IL-6 genes contribute to susceptibility to community-acquired and nosocomial pneumonia

Abstract: Genetic predisposition to CAP and NP is attributed to the cumulative contribution of polymorphisms at the CYP1A1, IL-6, and ACE genes, independently of age, gender, causative pathogen, and the use of mechanical ventilation, in patients in the Russian Federation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 45 publications
3
29
0
2
Order By: Relevance
“…A total of 12 eligible studies involving 5031 subjects were included in the meta-analysis. [7][8][9][10][11][12][13][14][15][16][17][18] The characteristics of selected studies are summarized in Table 1. There were four studies of Caucasians and seven studies of Asians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 12 eligible studies involving 5031 subjects were included in the meta-analysis. [7][8][9][10][11][12][13][14][15][16][17][18] The characteristics of selected studies are summarized in Table 1. There were four studies of Caucasians and seven studies of Asians.…”
Section: Discussionmentioning
confidence: 99%
“…5 So far, a number of studies have investigated the association of ACE I/D polymorphism with pneumonia. [7][8][9][10][11][12][13][14][15][16][17][18] Unfortunately, these epidemiological studies, performed in different countries, have yielded conflicting results, from strong links to no association. For instance, Morimoto et al indicated that the ACE DD genotype was associated with an increased risk of pneumonia and fatal pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is highly likely that these differences are the result of a complex interplay between both host and pathogen genetic backgrounds together with nongenetic factors, such as those discussed above [182]. With the recent development of fast and affordable high-throughput sequencing techniques, more studies have begun to explore the contributions of host genetics in the context of pneumonia [183][184][185][186]. The majority of these have focused on innate immune molecules, such as toll-like receptors and proinflammatory cytokines.…”
Section: Genetic Contributions To Pneumonia Risk and Severitymentioning
confidence: 99%
“…1. Overall, 10 original articles concerning the correlation of rs4340 SNP with pneumonia were considered eligible for this analysis [15,16,[22][23][24][25][26][27][28][29]. Main characteristics, including first author, publication year, study country, ethnicity of the populations included, assays used in determining rs4340 SNP, source of controls, specific type of pneumonia, and sample size, are presented in Table 1.…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
“…Recently, several studies indicate that the rs4340 genetic polymorphism was correlated with pneumonia predisposition [15,16]. However, this relationship remains controversial.…”
Section: Introductionmentioning
confidence: 99%